PENDEKATAN PLAY THERAPY DENGAN MENGGUNAKAN PERMAINAN TRADISIONAL PADA ANAK YANG KURANG BERSOSIALISASI (STUDI KASUS PADA KLIEN “R” DI DESA BULANG KECAMATAN BELIMBING - Yusi Kartika; Komaruddin; Neni Noviza (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
This thesis is entitled "The Play Therapy Approach Using Traditional Games for Less Socialized Children (Case Study on Client "R" in Bulang Village, Belimbing District)". The purpose of this study was to determine the social skills of client "R" before carrying out play therapy with traditional game techniques, to determine the process of implementing play therapy and to determine the sociability of client "R" after implementing play therapy using traditional games. This study uses qualitative research with a case study method. The data collection techniques are observation, interviews and documentation. The data analysis described by Robert K.Yin is pattern matching, explanation making and time series analysis. Research results 1) Client "R" includes children who are shy and quiet, the attitude of client "R" acts indifferent to the environment, has experienced rejection when playing and spends too much time playing gadgets, client "R" behaves aggressively towards himself, inferior, emotional instability and difficulty establishing communication. 2) Implementation of Relating (approaching process), Releasing (expressing client's thoughts and emotions), Re-creating (creating past and present client events), Reexperiencing (re- experiencing client events) and Resoving (solving problems with clients) , this forms the social, motoric, personality, cognitive and emotional development of client "R" through the traditional game of gobak sodor as an effort to form a confident attitude and eliminate shyness in client "R" so that he is able to interact through the form of a team in the game of gobak sodor the. 3) Client "R" begins to open up to the environment, the client begins to care about the team trying to keep the team winning in the game an attitude of openness, honesty and self-confidence for the client has started to grow. This shows that the client only has shame and is not confident, when persuaded first to take part in the game and because of encouragement as motivation, the client begins to dare to take part in the game and indirectly the client is able to socialize with his current environment.